Analysis of AS path looping - Sheng-lin ZHANG; Ying LIU (Tongxin xuebao)
AS (autonomous system) path looping occurs when there are two or more same AS numbers in a AS path vector and these numbers are not adjacent to each other.After processing and analyzing the global route data from RouteViews,statistics of the total number and the ratio of AS path looping conflicts were kept every day from June 1,2011 to May 31,2013.What’s more,distribution of the duration of AS path looping conflicts and the length of prefixes where AS path looping occurs were also analyzed.On the basis of these statistics,some possible causes of AS path looping were discussed,including routing information inconsistency,multi-national companies and faulty or malicious misconfiguration.What’s more,some advices were also provided for the configuration of BGP protocol.